The Plea Bargaining System as a Criminalization Model Under the Law Number 19 Year of 2016 on Electronic Information and Transaction Act and the Dignified Justice - Rinto Wardana (Global Legal Review, 2021)
From the perspective of economic analysis of law theory, the increasing number of criminal convictions  would indicate that the Indonesian  criminal Code and regulations have not been  effective in reducing the rate of crimes. By combining a preliminary hearing, hearing of cases through a special route and the application of the principle of bargaining for sentence in the plea bargaining system, a new mechanism may be formulated in the Indonesia criminal justice proceedings. This criminal justice approach employs the dignified justice principle (teori keadilan bermartabat) approach, whereby, the trial of cases using a preliminary hearing as a special route under a sole judge that is intended for an accused who pleads guilty and bargains for a sentence. Accordingly, this research attempts  to explore the use of the principles of the plea bargaining system as a criminal justice model under the Law Number 19 year of 2016 on the Electronic Information and Transaction Act (“EIT Act”). Equally important, this research employs the juridical-normative method, statute, case, and conceptual approaches in order to obtain a comprehensive result.